Design and development of solar desalination plant - Thaneissha, Marimuthu (2017)
Water which is crucial to living things on earth is the constituent of the environment. Our earth is rich with ocean which is also known as seawater. Yet, water crisis has become a serious problem that humanity facing nowadays especially in developing countries. Worldwide population expansion and industrial development have led to an enormous demand for fresh water supply. Therefore, we developed a solar desalination plant which can be the solution for this problem. Solar desalination refers to any process that eliminates some amount of salt and other minerals from saline water using sunlight. The objectives of this study are to design a low cost point focus parabolic solar still (PPSS) made up of non-fragile materials and to minimize the heat loss in this prototype by using heat exchanger. Our PPSS also entails of solar tracking system to capture the maximum amount of sunlight. The freshwater productivity was measured along the evaluation of the impacts of environment and operational parameters which includes solar irradiation, salinity and conductivity in December at Gambang, Pahang. The maximum productivity obtained is 170ml of fresh water where the average solar intensity for that day was 735.69W/m2. Our productivity is considered lower than the existing PPSS due to certain limitations such as weather condition, the size of the parabolic dish and absorber. From the results, it is found that the productivity of fresh water increases as the solar irradiation increases because the rate of evaporation depends on solar intensity and the weather. Finally, the sample has been analyzed before and after the desalination process to compare the salinity and conductivity. Through this process, PPSS is proven to be an effective method in reducing the salinity and conductivity in seawater. The freshwater obtained can be used for domestic purposes.